PENGARUH CITRA MEREK DAN KUALITAS LAYANAN TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN APLIKASI MAXIM PADA MASYARAKAT DI KOTA SEMARANG - Fadhioma Ammarendra; Ratih Hesty Utami Puspitasari; Rita Meiriyanti (CV. Denasya Smart Publisher, 2025)
Competition in online transportation services in Semarang City encourages companies to understand the factors that influence customer loyalty. Maxim, as one of the online transportation service providers, faces challenges in the form of customer complaints regarding the accuracy of pickup points, fare changes, and limited application features. This study aims to examine the effect of brand image and service quality on customer loyalty with customer satisfaction as a mediating variable. The research approach uses a quantitative method with a survey technique on 96 Maxim user respondents in Semarang City who were selected by purposive sampling. Data analysis was carried out using the Partial Least Square (PLS) technique with the help of SmartPLS 3.0 software. The results of the study indicate that brand image has a positive and significant effect on customer satisfaction, brand image does not affect loyalty, service quality has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on loyalty, customer satisfaction has a positive and significant effect on loyalty, brand image does not affect customer satisfaction and has an impact on loyalty, service quality affects customer satisfaction and has an impact on loyalty. The practical implication of the results of this study is the importance for Maxim to focus on improving its brand image and service quality, especially on the accuracy of pickup locations, tariff stability, and optimization of application features, in order to maintain and increase customer loyalty amidst competition in online transportation services.